2018
DOI: 10.47210/bjohns.2018.v26i3.209
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Hospital Acquired Infections among Patients in a Tertiary Care Hospital of Darjeeling District, West Bengal

Abstract: Introduction Hospital Acquired Infections (HAI), also called ‘Nosocomial Infections’ are identified at least 48-72 hours following admission to health institution. In many hospitals, HAI appears to be a hidden, cross-cutting problem. Thus a continuous surveillance is imperative for determining the extent of the problem and its effective prevention and control. Present study determines the incidence and different types of hospital acquired infections and the bacterial pathogens responsible for those. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…20,21 Our study is nearly dissimilar to the study of De et al in India (Gram-negative (66.3%) and Grampositive (33.6%); Kanj et al in Argentina (Gramnegative (81.8) and Gram-positive (18.2%). 11,22 This study observed mixed bacterial infection in 03 (07.69%) cases. It was similar to Alam in Bangladesh (10.20%).…”
Section: According To Grammentioning
confidence: 74%
See 3 more Smart Citations
“…20,21 Our study is nearly dissimilar to the study of De et al in India (Gram-negative (66.3%) and Grampositive (33.6%); Kanj et al in Argentina (Gramnegative (81.8) and Gram-positive (18.2%). 11,22 This study observed mixed bacterial infection in 03 (07.69%) cases. It was similar to Alam in Bangladesh (10.20%).…”
Section: According To Grammentioning
confidence: 74%
“…17,18 This finding differed from other studies like Amin et al in Bangladesh and De et al in India, which found around 22.7% and 19%, respectively. 19,11 The relatively high incidence of infections in this study may be due to poor nutritional status, poor adherence to aseptic measures, and high proportion of mechanical ventilation (Akter et al). 10…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A prevalence survey conducted under the World Health Organization (WHO) in 55 hospitals of 14 countries representing 4 WHO Regions (Europe, Eastern Mediterranean, South-East Asia and Western Pacific) showed an average of 8.7% of hospital patients had nosocomial infections. 3 The seven hospitals in the global infection control consortium had cumulative CAUTI infection rates of 1.41 per 1000 catheter days across seven Indian cities. 4 NI is a major factor in higher rates of morbidity, mortality, and financial burden in hospitals and other healthcare facilities.…”
Section: Introductionmentioning
confidence: 99%